Exploring the Effectiveness of Whatsapp Application on Teaching and Learning at One Midlands Teacher Education Institution in Zimbabwe - Shoorai Konyana; Motalenyane Alfred Modise (E-Journal of Humanities, Arts and Social Sciences)
Generally, social media platforms have been utilised to convey personal and non-academic information. Lecturers at higher education institutions have treated social media as a non-formal means of communication. However, with the advent of COVID-19-induced lockdowns, social media platforms gained importance in conveying both formal and non-formal information. This study thus analysed the effects of utilising the whatsapp platform for teaching and learning at one Midlands Teacher Education institution. Through the connectivism lens, the study adopted a qualitative case study generating data through interviews, observations and focus group discussions. Findings pointed to the fact that though sceptical about social media platforms in general, lecturers and students utilise whatsapp to a greater extent for online teaching and learning and for conveying important information. Most students own smartphones and Whatsapp, and though prone to cyberbullying and circulation of falsehoods, the platform was preferred to other platforms as it was categorised under cheaper modes of conveying information to many people at once. The study recommends that while integrating social media applications in teaching and learning, lecturers and students should verify the authenticity of social media information. This study contributes to the ongoing discourse on the use of blended learning and the possibility of utilising social media in educational contexts.